Optimalisasi Rantai Pasok Komoditas Pertanian Strategis di Jawa Timur - Ferry Prasetyia; Farah Wulandari Pangestuty; Andhika P. Herlambang (JSEP (Journal of Social and Agricultural Economics), 2022)
This study aims to identify value chain of strategic agricultural commodities in East Java. In addition, this study formulate supply chain optimization of strategic agricultural commodities in East Java. This study uses several analysis approaches, namely 1) input output analysis; 2) supply chain descriptive analysis, 3) supply chain management institutional pattern analysis, 4) trading margin analysis, 5) value chain analysis, 6) root problem analysis; and 7) Process Hierarchy Analysis (AHP).The results of this study indicate that there are three strategic commodities in East Java, namely sugar cane, cayenne pepper and corn. These strategic agricultural commodities have a fairly long supply chain. On average, producers (farmers/breeders) receive the lowest price margins among other supply chain actors. Collectors and wholesalers are known to receive the most margins.